TINJAUAN RELEVANSI CITY BRANDING MELALUI KOLABORASI BRAND INDEX DAN BRAND PERSONALITY: PADANG YOUR MOTHERLAND - Fitri Adona; Sri Nita; Yusnani Yusnani; Lut Mafrudoh (Jurnal Ilmiah Poli Bisnis, 2018)
This study applies the collaboration approach of city brand index and city brand personality towards the city branding "Padang Your Motherland". The results of city brand index show that the presence aspect - visitors 'views on international status and reputation globally' gets the highest rating. The aspect of the city brand index of the city of Padang that is relevant to the city branding "Padang Your Motherland" is the presence, place, people, sentiments of feeling, while the indirect is the potential and preconditions. On the other hand, City of Padang city personality scale also shows that some aspects that shape the brand personality of Padang City have direct relevance to the city branding "Padang Your Motherland", namely excitement, skill, and toughness, while the indirect aspects are sincerity and sophistication. This aspect that does not have direct relevance can be a supporter in the personality of Padang City. Based on the results of this study, it is suggested that the Padang City Government pay more attention to the potential aspects and prerequisites in city brand index and aspects of sincerity and sophistication in city brand personality in the development or evaluation of the city branding "Padang Your Motherland".